EVALUATION OF THE COST-EFFECTIVENESS OF THE PUBLIC SECTOR SERVICES: VARIABILITY OF THE METHODOLOGICAL TOOLS - Dyagel, Oksana Yurievna (Nauka Krasnoi͡a︡rʹi͡a, 2019)
The purpose of the article was to reveal the analytical tools for evaluating the effectiveness of the allocated financing funds for the provision of the services provided in the public sector of the economy, the application of which does not have a uniform methodology today. The possibility to solve this issue is shown with regard to the compulsory health insurance system. To achieve the goal, the study reveals the definition of such categories as “effect” and “efficiency” of the medical institutions activities, “efficiency of spending” of the Territorial Fund for Compulsory Health Insurance. There is revealed the analytical significance of the existing methodological approaches to assessing the effectiveness of health care costs; their comparative analysis is carried out. Based on the results, the alternative is proposed, based on the system of the cost-effectiveness indices to achieve the health, social and economic effects of medical institutions; the analytical advantages of the alternative proposed are justified.